Solid oxide fuel cell operating on liquid organic hydrogen carrier-based hydrogen – making full use of heat integration potentials. (18th January 2018) - Preuster, Patrick; Fang, Qingping; Peters, Roland; Deja, Robert; Nguyen, Van Nhu; Blum, Ludger; Stolten, Detlef; Wasserscheid, Peter
Abstract: Our contribution demonstrates the technological potential of coupling Liquid Organic Hydrogen Carrier (LOHC)-based hydrogen storage and hydrogen-based Solid Oxide Fuel Cell (SOFC) operation. As SOFC operation creates waste heat at a temperature level of more than 600 °C, clever heat transfer from the SOFC operation to the LOHC dehydrogenation process is possible and results in an overall efficiency of 45% (electric output of SOFC vs. lower heating value of LOHC-bound hydrogen). Moreover, we demonstrate that LOHC vapour does not harm the operational stability of a typical 150 W SOFC short stack. By operating the stack with LOHC-saturated hydrogen, operation times of more than 10 years have been simulated without noticeable degradation of SOFC performance. Highlights: SOFC operation with LOHC-stored hydrogen. Overall efficiency is 45%. LOHC vapour does not harm the SOFC.